Cervicotomy for the management of dystocia due to prepartum cervico-vagino prolapse and Incomplete Cervical Dilation (ICD) in cow: A case report - Newton Biswas; Brijesh Kumar; Mayank Singh Baghel; Chinmay Ruprao Warghat; MH Khan (Animal Reproduction Update, 2024)
A cow was presented to the Referral Veterinary Polyclinic, ICAR-IVRI, with a primary complaint of third-degree cervico-vaginal prolapse. All the vital parameters were within the normal range. A per-rectal examination revealed that the foetus was viable. Further, per-vaginal examination explored a dry vaginal passage with an incompletely dilated (2-finger) cervical rim. The animal was given dilation therapy along with periodic cervical massage and observed for 36 hours. There was no significant dilation of cervix (one feast) and first cervical ring which was relatively hard preventing the complete dilation, therefore, it was decided to opt for cervicotomy and live female calf had been delivered.